2020
DOI: 10.3390/polym12112460
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Hydroxypropyltrimethyl Ammonium Chitosan with Organic Acid: Synthesis, Characterization, and Antioxidant Activity

Abstract: A novel and green method for the preparation of chitosan derivatives bearing organic acids was reported in this paper. In order to improve the antioxidant activity of chitosan, eight different hydroxypropyltrimethyl ammonium chitosan derivatives were successfully designed and synthesized via introducing of organic acids onto chitosan by mild and non-toxic ion exchange. The data of Fourier Transform Infrared (FTIR), 13C Nuclear Magnetic Resonance (NMR), 1H NMR, and elemental analysis for chitosan derivatives in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…When dissolved in the water solution, the salt derivatives can dissociate into ionic forms, which means the higher positive charge density. Additionally, the positive charge is beneficial to scavenging radicals, because it can attract electrons of free radicals and inhibit their chain reaction [ 37 ]. Therefore, the antioxidant ability of salt derivatives is stronger than that of acylated derivatives.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When dissolved in the water solution, the salt derivatives can dissociate into ionic forms, which means the higher positive charge density. Additionally, the positive charge is beneficial to scavenging radicals, because it can attract electrons of free radicals and inhibit their chain reaction [ 37 ]. Therefore, the antioxidant ability of salt derivatives is stronger than that of acylated derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…For GLCOS and GL-COS, the new peaks appear at δ 6.87 ppm (a). For FUCOS, the new chemical shifts are present at δ 7.17 ppm (a), δ 7.11 ppm (b), δ 6.97 ppm (c), δ 6.77 ppm (d), δ 6.24 ppm (e), and δ 4.12 ppm (f), along with the same ones as FU-COS. For CMCOS and CM-COS, the new characteristic peaks are δ 6.23 ppm (a), δ 7.19 ppm (b), δ 7.38 ppm (c, d), and δ 6.78 (e, f) [ 37 ]. For CFCOS and CF-COS, the new chemical shifts are at δ 6.18 ppm (a), δ 7.13 ppm (b), δ 7.00 ppm (c), δ 6.91 ppm (d), and δ 6.77 ppm (e).…”
Section: Resultsmentioning
confidence: 99%
“… 56 However, the low bioactivity and poor water solubility of CS may greatly limit its clinical application. 57 Some studies have indicated that chemical modification can enhance the properties of CS without losing its unique characteristics, thus enabling a wider range of applications. 58 Therefore, structural and functional modifications of CS to obtain different CS derivatives with good water solubility and bioactivity are a focus of research.…”
Section: Research Progress In Nanoplatforms In the Treatment Of Dnmentioning
confidence: 99%
“…Therefore, cationic quaternary ammonium groups were introduced to the -OH position of Gel by etherification, preserving the biological activity and cross-linking site of -NH 2 (O-Gel). [25] In addition, gallic acid was coupled with O-Gel by ion exchange (O-Gel-Ga) [26] to impart antioxidant properties to the gel, while the catechol groups in gallic acid provide additional adhesion to the hydrogel. [27] To further enhance its mechanical properties and stability, sodium dialdehyde-alginate (ADA) was introduced to react with -NH 2 within modified Gel via a Schiff base reaction, [28] resulting in a double cross-linked interpenetrating hydrogel with excellent mechanical properties and self-healing properties.…”
Section: Introductionmentioning
confidence: 99%